Effect of Constrained Induced Movement Therapy on Functional Arm Reach Distance on Adult Hemiplegic Patients: A Pilot Study (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2022)
Background: Stroke is an acute onset of neurological dysfunction due to an abnormal cerebral vascular circulationwith resulting signs and symptoms that corresponds to focal area of brain. The most common characteristics ofMCA stroke are contra lateral spastic hemiparesis, motor and sensory disturbance of face, motor weakness of upperextremity and lower extremity with upper limb more affected than lower limb. Constraint induced movementtherapy (CIMT) involves ipsilesional limb restraint with training of paretic arm to overcome this learned disabilityby restraining the unaffected extremity and training the affected extremity.Aims and objectives of the study: To observe and analysis the effect of Constrained Induced Movement Therapyon hand function of chronic stroke patients.Data Analysis & Results: Shows that the pre and post intervention values of variable functional arm reach inchronic stroke patients of this study. In that mean values of pre and post intervention of functional arm reachwere 19.0 cm and 23.0 cm respectively. Results of significance p value were p≤0.05 explained that after constrainedinduced movement therapy intervention to the subjects the functional arm reach was improved statistically.Conclusion: This study concluded that Constraint Induced Movement Therapy (CIMT) shall have statisticallysignificant improvement on hand function of functional arm reach distance in adult hemiplegic patients.
Keywords: Functional Arm Reach, Chronic Stroke, Spasticity, Constraint Induced Movement Therapy.